Islamic perspectives on economic development - Tahir, Sayyid (Pakistan Institute of Development Economics, 1995)
This paper offers a restatement of the Islamic position while, at the same time, staying clear of downloading "Islamic values" into the mainstream thinking. In Section 1, the existing views of conventional and Islamic economists about economic development are noted. In Section 2, the Islamic concept of economic development is re-stated with direct reference to the Qur'an and the Sunnah (sayings and practice of the Prophet SAAWS. In Section 3, the argument of the previous section is reviewed along with the critical subjects of role of government and financing of development. In Section 4, some policy implications are noted, with Section 5 providing the concluding observation